DAYA TARIK WISATA PUSAT PELATIHAN BERKUDA IKHWAN KOTA PEKANBARU - Khadijah, Siti; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The Ikhwan Equestrian Training Center is the only riding training ground that provides horseriding tours in Pekanbaru City. Equestrian tour has a unique charm that visitors can see horsesas well as enjoy a fun experience while riding a horse, it becomes interesting for visitors whocome. To measure what the attraction of horse riding in this training center has met thestandard of attraction at a tourist destination, and this is measured from 4 components:attractions, accessibility, amenitas and support services. This research will be measured andknown by quantitative methods with observation data collection techniques, questionnairesand documentation. Samples or respondents taken as many as 30 respondents throughaccidental sampling technique. Based on the research that has been done, shows that thecharacteristics of visitors are mostly male, the characteristics of age at 10- 20 years, most ofthe students or students and derived from lolal visitors. results of processed data performedscores of tourist attraction in the medium category with a range of 700 - 1099 scores.Keywords: Attractiveness, Horse-riding Tour